2021
DOI: 10.1111/scd.12570
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of essential oil of cinnamon for the treatment of oral candidiasis: A randomized trial

Abstract: Aim: It was analyzed the efficacy of mouthwash and spray containing essential oil (EO) of Cinnamomum zeylanicum Blume for the treatment of oral candidiasis. Methods and results: A randomized, controlled, and blinded clinical trial was conducted with 36 individuals (probabilistic sample) with oral candidiasis who were divided into two treatment groups: C. zeylanicum (0.5 mg/mL), n = 18; nystatin (100,000IU/mL), n = 18. The efficacy of the products was evaluated by two parameters: (a) clinical evolution recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Prevention and management of coronavirus disease (COVID- 19) have not yet successful since no specific preventive measurement and treatment available. Therefore, searching for potential bioactive compounds from natural sources is an ongoing investigation as medicinal plants possess a tremendous antiviral compound.…”
Section: Antiviral Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention and management of coronavirus disease (COVID- 19) have not yet successful since no specific preventive measurement and treatment available. Therefore, searching for potential bioactive compounds from natural sources is an ongoing investigation as medicinal plants possess a tremendous antiviral compound.…”
Section: Antiviral Effectsmentioning
confidence: 99%
“…Therefore, research is urgently required to find alternatives to conventional medications for eradicating IDs. Natural products based therapy could be an excellent source of antimicrobial agents that would offer symptomatic relief since they have the high potentiality to inhibit the growth of microbes in the host-defence mechanism [4], as well as they offer promising outcomes in the scientific investigations [15][16][17][18][19][20]. Additionally, it would reduce unnecessary antibiotic prescription; therefore, the chances of antibiotic-resistance would be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the effects of mouthwash and spray containing cinnamon essential oil on Candida spp have been analyzed. A reduction of 61% and 33% of fungi isolates from oral mucosa and dentures, respectively, was noted, whereas the participants of the study reported a pleasant taste and only a few product-related complaints [ 79 ].…”
Section: Natural Sources Of Antimicrobial Compoundsmentioning
confidence: 99%
“…The antifungal properties of cinnamon are more pronounced than its antibacterial activity, indicating potential use in candidiasis treatments either as the main or a complementary agent [127][128][129][130]. De Araujo et al [131] analyzed the efficacy of mouthwash and spray containing essential oil of Cinnamomum zeylanicum Blume for the treatment of oral candidiasis. A mycological analysis demonstrated a reduction of 61% and 33% of Candida spp., isolated from oral mucosa and dentures, respectively.…”
Section: Natural Productsmentioning
confidence: 99%